Users' Definition of Snapchat Usage. Implications for Marketing on Snapchat. Issue 2 (3rd April 2019) - Tropp, Joerg; Baetzgen, Andreas
ABSTRACT: Despite its high popularity, Snapchat remains a mystery to many marketers. This study uses a mixed-methods approach to gain a thorough understanding of how users define Snapchat usage in terms of their cognitive processing and behavioral patterns. 14 core associations for Snapchat media usage were explored in focus groups, which were then converted into a consensus map using the concept map method (N = 96). Unlike previous studies, the findings suggest that Snapchat is not so much a medium for continuous communication with the consumer. Nevertheless, it can enrich relationships with them. Media usage is determined by hedonistic goals, while rational goals and normative constraints are in the background. Marketers should therefore focus their attention on aesthetic, affective and alternating stimuli.